1991
DOI: 10.3349/ymj.1991.32.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus caseisubspecies casei endocarditis: a case report

Abstract: Lactobacillus sp., generally considered to be a harmless indigenous bacteria of the mucous membrane, occasionally causes serious infections. Lactobacillus endocarditis is a very rare disease, and no case has been reported in Korea. Gram-positive bacilli were isolated from blood cultures of a 41-year-old man with clinically suspected subacute bacterial endocarditis. The patient had a dental procedure 3 months prior to the infection. The isolate was identified as L. casei subsp. casei based on the cultural chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…tient reported that he did not eat yogurt every day [6] and that he had not undergone dental manipulation before admission to the hospital [4,[7][8][9][10]. Laboratory tests revealed an erythrocyte sedimentation rate of 45 mm/h and a WBC count of cells/L (70% polymorphonuclear neutrophils).…”
mentioning
confidence: 99%
“…tient reported that he did not eat yogurt every day [6] and that he had not undergone dental manipulation before admission to the hospital [4,[7][8][9][10]. Laboratory tests revealed an erythrocyte sedimentation rate of 45 mm/h and a WBC count of cells/L (70% polymorphonuclear neutrophils).…”
mentioning
confidence: 99%
“…Lactobacillus endocarditis involved a substantial risk of relapse after medical therapy, and the occasional need for valve-replacement surgery to achieve cure (25,48). As in bacteremia cases L. casei group and also Lactobacillus plantarum were common findings in endocarditis (21,25,31,(48)(49)(50)(51)(52)(53)(54)(55). Like in the case of bacteremia, this reflects the common finding of these species in main sources of infection, rather than greater virulence (56).…”
Section: Endocarditismentioning
confidence: 85%
“…7 % ) . [2][3][4][5][6]8,10 Clinical course is characterized by fever, chills or night sweats, chest pain, shortness of breath, fatigue, and weakness. Important signs include paleness, carious teeth, precordial murmur, and an enlarged spleen.1-1O Diagnosis has been confirmed by positive blood cultures'-'° or by TTE or TEE demonstration of structural heart disease and/or vegetations.…”
Section: Discussionmentioning
confidence: 99%
“…Of 34 patients,8 (23.5%) have died, and among 21 who completed the full course of antibiotic therapy,8 (38.1 % ) have experienced a relapse.3,8-1O Five of the 8 with a relapse were cured with a second course of antibiotics.…”
mentioning
confidence: 97%